FAKTOR-FAKTOR YANG MENENTUKAN KEPUTUSAN WISATAWAN MENGINAP DI INAYA PUTRI BALI RESORT NUSA DUA - Ni Gusti Ayu Made Suryaningsih; Ni Made Hartini (Journal Research of Management, 2020)
Along with the development of the tourism industry in Bali, competition in hospitality industry also getting tighter, especially in Nusa Dua region. One of the five-star hotels in Nusa Dua area is Inaya Putri Bali Resort Nusa Dua. This study aims to know the factors that determine the decision of tourists and the dominant factors that determine the decision of tourists to stay at Inaya Putri Bali. Sample determination techniques used purposive sampling method. The respondents of this study were 100 tourists who stayed at Inaya Putri Bali. The results then analyzed with factor analysis techniques used SPSS version 21.0 for Windows. The analysis obtained 4 factors which explain 76.980% of the total variance factor. The factors that determine the decision of tourists to stay consist of 4 factors, namely: excellence, surplus value, supporting and marketing mix factors. The dominant factor that determines the decision of tourists to stay is the factor of excellence with an eigenvalue 10.142 and variance factor 50.709%. This study gave an overview to management of Inaya Putri Bali to improve excellence factors adn innovate factors outside of excellence factor in order to attract tourists to stay in the future.